Analysing Low-Income Incremental Housing through Spatial Design and Governance - Afua Wilcox (A+BE: Architecture and the Built Environment)
As cities across the globe grapple with rising urbanisation and housing shortages, over one billion people now reside in informal settlements. In South Africa, the legacy of apartheid planning, combined with systemic inefficiencies and rapid urban growth, has compounded the challenges of providing inclusive, sustainable low-income housing. While extensive research exists across disciplines such as architecture, political science, and economics, much of it remains siloed—offering fragmented perspectives on an inherently complex issue. This dissertation takes a different approach. It examines low-income housing through a double lens: spatial design—how built form is created and how its context is developed—and governance—the aims, actors, and instruments involved in decision making. Using the K206 housing project in Alexandra, Johannesburg, as a case study, the research explores what happens when government plans meet residents’ lived experiences. It engages three key literature themes of low-income housing: informal settlement upgrading, state-subsidised housing, and incremental housing. Through interviews, surveys, and expert consultations, the research reveals how governmental aims—such as resident-responsive design, security of tenure, and income generation—were translated into built form, and how residents responded to and reshaped these interventions—sometimes in unexpected ways.